2018
DOI: 10.1186/s12860-018-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA reduces SW837 colorectal cancer cell viability via the promotion of mitochondrial fission by activating JNK-Mff signaling pathways

Abstract: BackgroundMitochondrial homeostasis has been increasingly viewed as a potential target of cancer therapy, and mitochondrial fission is a novel regulator of mitochondrial function and apoptosis. The aim of our study was to determine the detailed role of mitochondrial fission in SW837 colorectal cancer cell viability, mobility and proliferation. In addition, the current study also investigated the therapeutic impact of Tanshinone IIA (Tan IIA), a type of anticancer adjuvant drug, on cancer mitochondrial homeosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…31 Furthermore, Mff-induced mitochondrial fission was attributed to decreased colorectal cancer cell viability. 32 Our findings showed that Mff was a key molecule participating in mitochondrial fission, contributing to CDDP sensitivity in hypoxia-cultured HNSCC cells. Both Mff and Mfn2 expression were upregulated in HNSCC tissues, indicating that mitochondrial dynamics in tumor tissues are more active than that in normal tissues.…”
Section: Discussionmentioning
confidence: 54%
“…31 Furthermore, Mff-induced mitochondrial fission was attributed to decreased colorectal cancer cell viability. 32 Our findings showed that Mff was a key molecule participating in mitochondrial fission, contributing to CDDP sensitivity in hypoxia-cultured HNSCC cells. Both Mff and Mfn2 expression were upregulated in HNSCC tissues, indicating that mitochondrial dynamics in tumor tissues are more active than that in normal tissues.…”
Section: Discussionmentioning
confidence: 54%
“…[29] Furthermore, Mff-induced mitochondrial ssion was attributed to decreased colorectal cancer cell viability. [30] Our ndings showed that Mff was a key molecule participating in mitochondrial ssion, contributing to CDDP sensitivity in hypoxia-cultured HNSCC cells. Both Mff and Mfn2 expression were upregulated in HNSCC tissues, indicating that mitochondrial dynamics in tumor tissues are more active than that in normal tissues.…”
Section: Discussionmentioning
confidence: 66%
“…One of the most important bioactive constituent of the medicinal plant Salvia miltiorrhiza is Tan IIA, which has been widely used in the treatment of cardiovascular, cerebrovascular, and neoplastic disorders. [17][18][19] As mentioned, this compound exhibits multiple anti-neoplastic mechanisms, including inhibiting tumor cell proliferation, 20 invasion, and metastasis, 21 and induction of apoptosis. 22 However, the therapeutic molecular mechanisms of Tan IIA in the context of CRC remain incompletely known.…”
Section: Discussionmentioning
confidence: 98%